2017
DOI: 10.1111/sji.12558
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Roles of Th17 and Th1 Cells in Inflammatory Responses Associated with the Presentation of Paucibacillary Leprosy and Leprosy Reactions

Abstract: It is well established that helper T cell responses influence resistance or susceptibility to Mycobacterium leprae infection, but the role of more recently described helper T cell subsets in determining severity is less clear. To investigate the involvement of Th17 cells in the pathogenesis of leprosy, we determined the immune profile with variant presentations of leprosy. Firstly, IL-17A, IFN-γ and IL-10 were evaluated in conjunction with CD4 T cell staining by confocal microscopy of lesion biopsies from tube… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 39 publications
(71 reference statements)
1
31
0
Order By: Relevance
“…We did identify elevated IL-17A levels in WBA with HHC than those using MB samples. A previous study by our group found an association of Th17 response with the milder PB forms of leprosy (16). Taken together, our data indicate a broader and more robust anti-mycobacterial immune response in HHC than that of patients.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…We did identify elevated IL-17A levels in WBA with HHC than those using MB samples. A previous study by our group found an association of Th17 response with the milder PB forms of leprosy (16). Taken together, our data indicate a broader and more robust anti-mycobacterial immune response in HHC than that of patients.…”
Section: Discussionmentioning
confidence: 69%
“…There is now strong associative evidence that the genetic background and immunological response of the infected individual influence both susceptibility to M. leprae infection and outcome of leprosy (2, 4, 8, 9). Antigen-specific T helper 1 (Th1) and T helper 17 (Th17) cells are observed in paucibacillary (PB) patients and are associated with control of M. leprae replication (2, 816). In contrast, T helper 2 (Th2) and T regulatory (Treg) cells are associated with the multibacillary (MB) presentations that are characterized by heavily infected macrophages and multiple skin lesions (14, 15, 17).…”
Section: Introductionmentioning
confidence: 99%
“…Santos et al . 10 observed that reactional multibacillary patients presented highest concentrations of serum IFN-γ. Likewise, Motta et al .…”
Section: Discussionmentioning
confidence: 95%
“…Appropriate innate and adaptive immune response interactions can influence the clinical outcome of leprosy, and recent studies suggest that higher serum IFN-γ concentrations are related to the development of leprosy reactions in individuals with the multibacillary form 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%
“…5 The termination of leprosy transmission depends on several aspects such as microbiological aspects, environmental factors, and immunological aspect. 7,8 A good immune system needs to be nourished from the beginning of life by improving perinatal health status of both mother and child. 5 Previously, four subset of T cells, namely Th1, Th2, Th17, and Treg were known to play roles in human immune response against leprosy.…”
Section: Introductionmentioning
confidence: 99%